Inequalities in infant vaccination coverage during the COVID-19 pandemic: A population-based study in Peru - Al-kassab-Córdova, Ali (2023)
Objective: To identify the associated factors and assess the inequalities of full vaccination coverage (FVC) among Peruvian infants aged 12–23 months during the COVID-19 pandemic in a nationally representative sample. Methods: We carried out a population-based cross-sectional study based on a secondary data analysis using the 2021 Peruvian Demographic Health Survey (DHS) in infants aged 12 to 23 months. The sampling design was probabilistic, multistage, stratified, and independent at both departmental and area of residence levels. FVC was defined according to the WHO definition. We performed generalized linear models (GLM) Poisson family log link function to estimate crude (aPR) and adjusted prevalence ratios (aPR). Also, for inequality assessment, we calculated the concentration curve (CC), concentration index (CI), and Erreygers normalized concentration index (ECI). Results: We included 4,189 infants in our analysis. Nationwide, the prevalence of FVC was 66.19% (95% CI: 64.33–68). Being younger, having a mother with no education or primary education, belonging to a large family, having no access to mass media, having had six or fewer ANC visits, and having a mother whose age was under 20 at first delivery were inversely associated with FVC. Meanwhile, living in the Highlands or on the rest of the coast, and living in rural areas were directly associated with FVC. We found a pro-rich inequality in FVC based on wealth-ranked households (CI: 0.0066; ECI: 0.0175). Conclusion: FVC has dropped among Peruvian infants aged between 12 and 23 months. There were several factors associated with FVC. It was more concentrated among the better-off infants, although in low magnitude.